Formation of alumina-aluminide coatings on ferritic-martensitic T91 steel - Choudhary R.K.; Kain V.; Hubli R.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, alumina-aluminide coatings were formed on ferritic-martensitic T91 steel substrate. First, coatings of aluminum were deposited electrochemically on T91 steel in a room temperature AlCl3-1-ethyl-3-methyl imidazolium chloride ionic liquid, then the obtained coating was subjected to a two stage heat treatment procedure consisting of prolonged heat treatment of the sample in vacuum at 300 ○C followed by oxidative heat treatment in air at 650 ○C for 16 hours. X-ray diffraction measurement of the oxidatively heat treated samples indicated formation of Fe-Al and Cr-Al intermetallics and presence of amorphous alumina. Energy dispersive X-ray spectroscopy measurement confirmed 50 wt- % O in the oxidized coating. Microscratch adhesion test conducted on alumina-aluminide coating formed on T91 steel substrate showed no major adhesive detachment up to 20 N loads. However, adhesive failure was observed at a few discrete points on the coating along the scratch track.